Issues in the Implementation of the “Merdeka” Curriculum in Junior High Schools in Ambon City - Tanwey Gerson Ratumanan; Jolanda Tomasouw; Petrus J Pattiasina; Fricean Tutuarima (Nexus Publishing, 2026)
This study aims to identify junior high school teachers’ understanding of the Merdeka Curriculum and the challenges encountered in its implementation in Ambon City. The research was conducted in 14 junior high schools, including eight public and six private institutions, involving a total of 66 respondents—14 school principals and 52 teachers. A mixed-method approach combining quantitative descriptive and qualitative analysis was employed. The findings reveal that: (1) Teachers in Ambon’s junior high schools demonstrate a relatively high level of understanding of the Merdeka Curriculum, with an average score of 87.6%. (2) All junior high schools (100%) have adopted the Merdeka Curriculum and developed their respective Operational Curriculum of the Education Unit documents. Schools report an average of 10 extracurricular activities, showing a tendency toward increased student involvement. The Pancasila Student Profile Strengthening Project (P5) has been implemented in 92.86% of schools, with themes tailored to each school’s context. (3) The curriculum's implementation has had a positive impact, enhancing teacher performance, creativity, and overall learning quality. (4) However, several challenges persist, including 17.14% of schools not yet implementing the P5 program; teachers’ limited ability to design integrated strategies for developing literacy and numeracy; suboptimal use of information and communication technology; and difficulties in creating assessment instruments that effectively balance comprehension, application, and reasoning. The study highlights the need for ongoing training and support to ensure effective and sustainable implementation of the Merdeka Curriculum in junior high schools.